A Critique to the Theory of "US Government Targeted Killings" in the Light of the Fundamental Principles and Procedures of International Humanitarian Law - Mahdi Hatami (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In recent years, the US government has pursued a policy of targeted killings of those suspected of committing terrorist acts. This policy is often referred to as a legitimate and necessary response to terrorism and asymmetric wars. In this article, we seek to examine the conformity of targeted killings with the findings of international law by examining this practice in the light of international law standards and, in particular, international humanitarian law. This policy is applied both to armed conflict and to peace. Therefore, in criticism and legal analysis of targeted killings, the requirements of international humanitarian law as well as the findings of human rights are emphasized and the application of such a function is examined and analyzed within the framework of these principles. After analyzing and elaborating on this case, the author concludes that targeted killings do not comply with humanitarian rights standards and it is necessary to prevent the establishment and legitimization of this phenomenon and to legitimize it within the framework of international law of international protest and condemnation.